Diagnóstico y manejo de la malaria cerebral causado por plasmodium falciparum. - Arcentales Andrade, Carlos Anibal (Machala : Universidad Técnica de Machala, 2019)
Malaria is a pathology that has a high mortality rate worldwide, in 2016 216 million cases were reported, one of its Objective: complications is cerebral malaria with a higher incidence in children under 5 years. Differentiating this disease from others is complicated because it also requires clinical assessment and laboratory tests complementary studies such as magnetic resonance, transcranial Doppler echo that are still under study. To know the diagnostic methods and the updated management of cerebral malaria caused by Plasmodium falciparum, through the analysis of indexed scientific articles, in order to contribute to the proper management of this pathology. Method: It is a descriptive study, by which data base information was used as: Science Direct, pubmed, elservier, New England and Google Scholar for the search of scientific articles of the last 5 years. Conclusion: Cerebral malaria is a serious disease that requires constant monitoring of patients. The treatment of malaria should be used antiparasitic treatment, adjuvant therapy and supportive care. Despite the research carried out, the pathogenesis of cerebral malaria remains to be established, which hinders the development of complementary therapies.
La malaria es una patología que tiene un alto índice de mortalidad a nivel mundial, en el 2016 se reportaron 216 millones de casos, una de sus complicaciones es la malaria cerebral con una incidencia mayor en niños menores de 5 años. Diferenciar esta enfermedad de otras es complicada porque requiere además de valoración clínica y de exámenes de laboratorio estudios complementarios como resonancia magnética, eco doppler trancraneal que aún se encuentran en estudio. Objetivo: Conocer los métodos diagnósticos y el manejo actualizado de la malaria cerebral provocado por Plasmodium falciparum, mediante el análisis de artículos científicos indexados, para poder contribuir en el manejo adecuado sobre esta patología. Método: Es un estudio tipo descriptivo, mediante el cual se usó información de base de datos como: Science Direct, PubMed, ElSERVIER, NEW England y Google Académico para la búsqueda de artículos científicos de los últimos 5 años. Conclusión: La malaria cerebral es una enfermedad grave que requiere vigilancia constante de los pacientes. El tratamiento de la malaria se debe utilizar tratamiento antiparasitario, terapia coadyuvante y cuidados de apoyo. A pesar de las investigaciones realizadas la patogenia de la malaria cerebral queda por establecerse lo que dificulta el desarrollo de terapias complementarias.
Keywords: PLASMODIUM FALCIPARUM; MALARIA CEREBRAL; METODOS DE DIAGNOSTICO; TRATAMIENTO